Ethical Considerations in Multiple Pregnancy: Preterm Delivery in the Setting of Discordant Fetal Anomaly. (26th April 2019) - Phillips, Thérèse; Moore, Bryanna; Posma, Elske; Gillam, Lynn; Cuzzilla, Rocco; Cole, Stephen
Abstract: Planning for the preterm birth of a fetus with known anomalies can raise complex ethical issues. This is particularly true of multiple pregnancies, where the interests of each fetus and of the expectant parent(s) can conflict. In these complex situations, parental wishes and values can also conflict with the recommendations of treating clinicians. In this article, we consider the case of a dichorionic twin pregnancy complicated by the diagnosis of vein of Galen aneurysmal malformation (VGAM) in one of the twins at 28 weeks' gestation. Subsequent deterioration of the affected twin prompted the parents to request preterm delivery to prevent the imminent in-utero demise of the affected twin. However, given the associated risks of prematurity, complying with the parents' request may have disadvantaged the health and wellbeing of the unaffected twin. This article canvases the complex ethical issues raised when parents request preterm delivery of a multiple pregnancy complicated by a fetal anomaly in one twin, and the various ethical tools and frameworks that clinicians can draw on to guide their decision-making in such cases.